Macrolinguistic analysis of discourse in TBI: Right vs left hemisphere injury - N, Hema; K C, Shyamala (Journal of All India Institute of Speech and Hearing, 2013)
The present study aimed to assess and compare the macrolinguistic ability of discourse in terms of coherence measurement in predominantly right and left hemisphere injured participants among a group of traumatic brain injured (TBI). The participants included 10 each of right and left hemisphere injured. The sample for the study included elicited gist of the picture of a picnic spot taken from Western Aphasia Battery (Shyamala & Ravikumar, 2008). An attempt was made to infer the coherence ability using the macrolinguistic analysis of discourse. For the same, Discourse Analysis Scale (Hema & Shyamala, 2008) for picture description task was used to measure the time duration taken to tell the gist of the picture and this latency value was determined for each of the participants using Wave Surfer 1.5.7 computer software. The time taken to give the gist of the given picture was measured in terms of seconds. The results of the study showed a significant difference in the duration value between the TBI participants with left hemisphere injury and right hemisphere injury statistically. But the mean value for right hemisphere injured participants among the TBI group was higher which suggests that the former group took more time to give the gist of the picture compared to left hemisphere injured participants among the TBI group. The picture description task can be used as a means of eliciting discourse samples to identify the factors contributing cognitive-communication impairments. Thus, the cognitive processing speed of coherence can be inferred by using macrolinguistic analysis in TBI discourse which is important for theoretical and clinical consideration pertaining to diagnosis and management. Reaction time could be an important measure pertaining to coherence. However, this finding needs further research support.